2013
DOI: 10.1111/jpi.12075
|View full text |Cite
|
Sign up to set email alerts
|

The role of melatonin in the cells of the innate immunity: a review

Abstract: Melatonin is the major secretory product synthesized and secreted by the pineal gland and shows both a wide distribution within phylogenetically distant organisms from bacteria to humans and a great functional versatility. In recent years, a considerable amount of experimental evidence has accumulated showing a relationship between the nervous, endocrine, and immune systems. The molecular basis of the communication between these systems is the use of a common chemical language. In this framework, currently mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
296
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(306 citation statements)
references
References 237 publications
(307 reference statements)
7
296
1
2
Order By: Relevance
“…Melatonin (N-acetyl-5-methoxytryptamine) in mammals is synthesized in several cells, tissues, and organs mainly for local utilization (autocrine and paracrine actions) and the circulating melatonin is mostly provided by the pineal gland [11,12]. It is known that melatonin is responsible for regulation of circadian rhythms, immune responses and mood, and reduces oxidative stress [13][14][15][16]. The roles of melatonin in obesity management have been studied in animal models of diet-induced obesity.…”
Section: A Double-blind Placebo-controlled Trial Related To the Effementioning
confidence: 99%
“…Melatonin (N-acetyl-5-methoxytryptamine) in mammals is synthesized in several cells, tissues, and organs mainly for local utilization (autocrine and paracrine actions) and the circulating melatonin is mostly provided by the pineal gland [11,12]. It is known that melatonin is responsible for regulation of circadian rhythms, immune responses and mood, and reduces oxidative stress [13][14][15][16]. The roles of melatonin in obesity management have been studied in animal models of diet-induced obesity.…”
Section: A Double-blind Placebo-controlled Trial Related To the Effementioning
confidence: 99%
“…Similarly, a number of studies have found melatonin plays a fundamental role in immune-modulation, but this has been explored almost exclusively in vertebrates (for recent reviews see [71][72][73]). The immune-modulatory effect of melatonin on the adaptive vertebrate immune system is supported by the existence of specific melatonin receptors in immune organs as well as immunocompetent cells, with its role in innate immunity recently proposed [71]. This latter finding is of particular interest from the invertebrate perspective, because while invertebrates lack an adaptive immune response, their innate immune system, particularly that of the insects, is highly effective and has cellular recognition and defensive pathways that are comparable with vertebrates (for a comprehensive coverage of the discipline see [74]).…”
Section: (B) Melatonin and Circadian Rhythmmentioning
confidence: 99%
“…Melatonin supplementation experiments generally reveal a positive effect of melatonin on survival in both vertebrates and invertebrates [67][68][69][70]. Similarly, a number of studies have found melatonin plays a fundamental role in immune-modulation, but this has been explored almost exclusively in vertebrates (for recent reviews see [71][72][73]). The immune-modulatory effect of melatonin on the adaptive vertebrate immune system is supported by the existence of specific melatonin receptors in immune organs as well as immunocompetent cells, with its role in innate immunity recently proposed [71].…”
Section: (B) Melatonin and Circadian Rhythmmentioning
confidence: 99%
“…Many of the effects of melatonin on the immune system and on inflammation also are mediated by nf-κB [74,87,88]. Melatonin reduces nf-κB binding in spleen [89].…”
Section: Melatonin/ubiquitin Interaction In Brown Fatmentioning
confidence: 99%